Diel changes and diversity of pufM expression in freshwater communities of anoxygenic phototrophic bacteria - Fecskeová, Lívia Kolesár; Piwosz, Kasia; Hanusová, Martina; Nedoma, Jiří; Znachor, Petr; Koblížek, Michal (Scientific reports, 2019)
The anoxygenic phototrophic bacteria (APB) are an active component of aquatic microbial communities. While DNA-based studies have delivered a detailed picture of APB diversity, they cannot provide any information on the activity of individual species. Therefore, we focused on the expression of a photosynthetic gene by APB communities in two freshwater lakes (Cep lake and the Římov Reservoir) in the Czech Republic. First, we analyzed expression levels of pufM during the diel cycle using RT-qPCR. The transcription underwent a strong diel cycle and was inhibited during the day in both lakes. Then, we compared DNA- (total) and RNA-based (active) community composition by sequencing pufM amplicon libraries. We observed large differences in expression activity among different APB phylogroups. While the total APB community in the Římov Reservoir was dominated by Betaproteobacteria, Alphaproteobacteria prevailed in the active library. A different situation was encountered in the oligotrophic lake Cep where Betaproteobacteria (order Burkholderiales) dominated both the DNA and RNA libraries. Interestingly, in Cep lake we found smaller amounts of highly active uncultured phototrophic Chloroflexi, as well as phototrophic Gemmatimonadetes. Despite the large diversity of APB communities, light repression of pufM expression seems to be a common feature of all aerobic APB present in the studied lakes.
Keywords: fotoperioda; Bacterial Proteins; fylogeneze; Lakes; mikrobiota; Alphaproteobacteria; Česká republika; Betaproteobacteria; Phylogeny; Photoperiod; Microbiota; regulace genové exprese u bakterií; jezera; světlo; Czech Republic; DNA, Bacterial; DNA bakterií; fototrofní procesy; Phototrophic Processes; bakteriální proteiny; fotosyntetická reakční centra (proteinové komplexy); Light; Photosynthetic Reaction Center Complex Proteins; Gene Expression Regulation, Bacterial